Enolase 1 differentially contributes to cell transformation in lung cancer but not in esophageal cancer - Chen, Jo‑Mei; Chiu, Shao‑Chih; Chen, Kun‑Chieh; Huang, Yun‑Ru; Liao, Yu‑Ting; Yu, Chang‑Tze (Oncology letters, 2020)
Enolase transforms 2-phospho-D-glycerate into phosphoenolpyruvate during glycolysis. The human enolase (ENO) family comprises three members named ENO3, which is restricted to muscle tissues, ENO2, which is neuron- and neuroendocrine tissue-specific, and ENO1, which is expressed in almost all tissues. ENO1 is involved in various types of human cancer, including retinoblastoma, hepatocellular carcinoma, pancreatic cancer, renal cell carcinoma, cholangiocarcinoma and gastric cancer. Furthermore, ENO1 enhances cell transformation in numerous cancer cell lines. It has been reported that ENO1 is involved in various activities that are detrimental to cell transformation, including apoptosis and differentiation. However, a few studies demonstrated that ENO1 can be down- or upregulated in various types of lung cancer, which suggests that ENO1 has an ambiguous role in the development of lung cancer. The present study aimed to investigate the differential influences of ENO1 on various types of cancer, and to clarify the role of ENO1 in lung cancer in particular. Western blotting was performed to assess ENO1 protein expression levels in lung cancer and esophageal cancer tissues. Furthermore, exogenous ENO1 was overexpressed in cell lines derived from various tissues and single cell proliferation, flowcytometric analysis, and western blotting were performed to determine the cell proliferation rate, cell transformation status, cell cycle progression and the expression of cell cycle regulators, such as cyclins and cyclin-dependent kinases, and survival factors, such as MAPK and AKT. The results demonstrated that ENO1 was upregulated in collected panels of lung cancer tissues, but not in esophageal cancer tissues. In addition, overexpression of ectopic ENO1 promoted cell proliferation and survival in lung cancer cell lines, which was not the case in other cells, including an esophageal cell line. Furthermore, mechanistic analyses revealed that ENO1 enhanced cell proliferation by accelerating G progression and upregulating G phase cyclin-dependent kinase 6 (CDK6), and improved cell survival by upregulating p38 in the MAPK cascade and increasing p-AKT in the AKT cascade, in particular in lung cancer cell lines. Overall, the results from the present study demonstrated that ENO1 may contribute to the development of lung cancers, but not esophageal cancers.